Group dynamics and relocation decisions of a trap-building predator are differentially affected by biotic and abiotic factors. Issue 6 (16th January 2017) - Katz, Noa; Shavit, Roni; Pruitt, Jonathan N; Scharf, Inon
Abstract: Most habitats in nature are heterogeneous, incorporating favorable and unfavorable microhabitats for different animals, based on their ecological niche. Unsuitable microhabitats have negative consequences for individual growth and survival. Animals, therefore, should fine-tune their location within the habitat by dispersing away from such microhabitats. We studied the suitability of different constant microhabitat conditions for wormlion larvae, a trap-building predator, tested in groups under laboratory conditions. Wormlions construct pit-traps in loose soil and capture small arthropod prey. As wormlions occur in high densities in nature, testing in groups is thus more indicative of their natural behavior than testing individuals. Wormlions responded strongly to biotic conditions—high conspecific density, starvation, and large body mass of conspecifics—by either increasing pit-relocation events or moving away from the microhabitat center to the periphery of the arena, probably opting for a way out. In other instances, individuals increased their distance to the nearest neighbor, thereby changing the spatial pattern toward a more regular pattern, potentially indicating interference competition. The only abiotic condition apparently perceived by wormlions as unsuitable was shallow sand, which led to frequent relocations. The two other abiotic factors—illumination and sand particle size—had no observable effect on behavior, although wormlions in nature always occur under shade in fine sand, and prefer both shade and fine sand particle size under laboratory conditions when given a choice. Under the fine spatial scale of the present experiment, biotic factors appear to be more influential than abiotic ones.